Reduction of Peak Power in ofdm Signal Using Cyclic Shifting in Partial Transmit Method. Issue 1 (March 2021) - Deepa, D.; Poongodi, C.; Sandhiyadevi, P.; Mohanapriya, G.K.
Abstract: Nowadays, multiplexing the frequency in orthogonal manneris the major concern for high speed data requirements in communication system. It has many advantages like achieving high speed data rate, resilience to frequency fading nature and highly tolerance to interferences and more flexible for implementing with other systems. Also, this OFDM system utilizes maximum bandwidth and will reduce the co-channel interferences. But the main back lock in OFDM system is peak to average power ratio(PAPR) which makes the waveforms more distorted which leads to need of high-power amplifiers in system design. In order to control this back lock, many techniques are proposed, but it has complexity problem. In this work we proposed a partial transmit sequence method along with cyclic shift sequences without performing phase rotation during the process. The simulation results show the high efficiency in PAPR reduction problem when compared to the other systems and it shows the less computation complexity during implementation.